Making connection between CEMAC and UEMOA countries by using a new method of data analysis - (:unkn) unknown (My University, 2021)
We present a dual version of the CONCORG method called CONCORGD. This method is proposed in the context of two groups of partitioned individuals measured on the same set of variables, that means two vertical multi-tables. The CONCORGD method is used for making connection between the data of the Economic and Monetary Community of Central Africa (CEMAC) and the Economic and Monetary Union of West Africa (UEMOA).
Keywords: African Research